FILM RELIGI SEBAGAI MEDIA DAKWAH ISLAM - M. Ali Musyafak (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
As a mass media, a movie is used as a means that reflects the reality of people and even by itself creates reality and public opinion. A film is not only a means of entertaining program, but it can help to demonstrate visually and dynamically. Besides, it is a tool to convey messages that becomes more vivid or realistic than merely the use of words or writings. In addition, film also able to provide confirmation of the conveyed materials for the audience to be more focused on the broadcasted content. Further, by displaying the Islamic culture and give massage of salvation and peace to the mankind, religious films increasingly get recognized as an important entity that must deserve special attention from the Muslims specially those who are engaged in propagation or da’wah activities in order to save human life and the people. According to the mission and the message of Islam, it is a religion of blessing to all human being (rahmatan li al– Alamin). In addition, the messages must be gently and smartly delivered to the audience without their feeling of being patronized. In addition, religious film can also become a touching movie on the affective side of human nature through spiritual and intuitive metaphors, logic and audio visual aesthetic language.